Dymanics Of Public Trust In Government Institutions In The Post-Truth Era: An Analysis Of The Role Of Social Media In Perception Formation - Larisu, Zulfiah; Rudi, Rudi (Socious Journal, 2025)
The post-truth era is characterized by a decline in the authority of objective truth due to the dominance of emotion-based narratives and subjective beliefs. In the context of government, this phenomenon exacerbates the crisis of public trust, especially with the massive spread of misinformation and disinformation through social media. Political polarization reinforced by digital algorithms further hampers government communication in conveying fact-based information. This study aims to analyze the dynamics of public trust in government institutions in the post-truth era using a descriptive qualitative approach. Data were collected through in-depth interviews, social media content analysis using the Netnography method, and related document studies. The results of the study show that social media plays a dual role as a transparency platform as well as a propaganda tool that can manipulate public opinion. The spread of disinformation is faster than official government communication, causing increased public skepticism. Therefore, the government's communication strategy must be oriented towards transparency, digital literacy, and public participation in order to rebuild legitimacy. Collaboration between the government, media, and academics is key to creating a healthy information ecosystem. With an adaptive communication approach, the government can overcome the challenges of the post-truth era and restore public trust sustainably.